Germination Studies on Arid Zone Tree Seeds I. Acacia senegal Willd. - Kaul, R. N.; Manohar, Man Singh (Indian Forester, 1966)
Seeds of Acacia senegal should be collected when the pods begin to become bronze in colour (10 days after appearance of green pods filled with seed) so as to obviate the necessity of seed scarification and in order to obtain maximum germination percentage. Further the moisture condition of the seed bed should not be allowed to fall below-600 Joules/kg during the germination period as beyond this point the germinability is severely affected irrespective of the extent of seed maturity.